Hedging hedge fund portfolio returns with Vix Index - Kärkkäinen, Heidi (My University, 2008)
Purpose of this thesis is to compare the relationship of hedge fund portfolio and Vix index as well as to explore whether Vix index allocation is able to hedge hedge fund portfolio from downside movements in the negative months of hedge fund portfolio. Credit Suisse/Tremont Hedge Fund index is used as the hedge fund portfolio. The data of hedge fund index and Vix index has 156 monthly observations from 1994-2006. The Chicago Board of Options Exchange (CBEO) Volatility Index (VIX) is a measure of implied volatility derived from S&P 500 options prices. Motivation of this thesis is to provide useful information of hedge fund’s characteristics and special features to investors and hedge fund managers. Hypotheses of this thesis were set based on the findings in the earlier studies of hedge funds. The first hypothesis suggested that Vix index is negatively correlated with hedge fund returns. The second hypothesis was set that a slight allocation of Vix index to hedge fund portfolio, in negative months of hedge fund returns, reduces risk and protects from downside movements. Study was started by analyzing the hedge fund data and it was found that hedge funds have characteristics that traditional methods estimating risk and returns are not appropriate for hedge funds. It was seen that hedge fund returns are skewed and are not clearly normally distributed. Highly negative correlation was also found of hedge fund portfolio and Vix index supporting the first hypothesis of this thesis. Purpose of the second hypothesis was to found a Vix index allocation to hedge fund portfolio which would hedge from downside movements in the negative months of hedge funds. Wilcoxon signed rank test and Value at Risk analysis gave a Vix index allocation which would be either 20% or about 10% depending on purpose of the hedging. The second hypothesis was supported.
Keywords: hedge funds; Vix index; portfolio allocation; volatility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|